Peningkatan Keterampilan Libreoffice Untuk Santri Pondok Pesantren Syaikh Zainuddin Nahdlatul Wathan - Ahmad Ashril Rizal; M. Saleh Sofyan; Lalu Puji Indra Kharisma; Muh. Fahrurrozi (Yayasan Lavandaia Dharma Bali, 2023)
Nahdlatul Wathan was founded with a determination to strengthen the education sector in the archipelago. Not only education, but NW also strengthens the economic, social, science and information technology sectors. Information technology is developed with formal and non-formal methods.In its formal form, NW established a university in the field of information technology. In the non-formal sector, communities also strengthen soft skills in the field of information technology. One of them is support for increasing the ability to use office applications for students and female students at the Nahdlatul Wathan Anjani Islamic boarding school. However, Islamic boarding schools provide students with microsoft office skills.There is nothing wrong with using Microsoft Office in general. The problem occurs because the office applications that are used are almost all pirated office applications.LibreOffice can be an alternative to using open source office applications. LibreOffice is a suite of office applications developed by The Document Foundation. With the Libreoffice skills workshop for the Santri at the Syaikh Zainuddin Nahdlatul Wathan Islamic Boarding School, it is hoped that it can help students become easy to use open source applications.The hope is that Indonesia can be free from application piracy. The results of the post-test at the post-workshop showed that the participants were able to complete the module well. In the post-test libreoffice writer 92.89% completed the module correctly, 83.63% on libreoffice calc, 94.72% on libreoffice impress and 92.12% on libreoffice draw